Correction to “An Electrochemical Sensor for Quantitation of the Oral Health Care Agent Chlorogenic Acid Based on Bimetallic Nanowires with Functionalized Reduced Graphene Oxide Nanohybrids” - Li, Wei; Deng, Xiuli; Wu, Ziyu; Zhang, Louqiang; Jiao, Jian (ACS omega, 2023)
[This corrects the article DOI: 10.1021/acsomega.1c06612.].